Bem-estar e Resiliência em habitação social: uma relação necessária – estratégias para sua obtenção orientadas aos usuários - Araujo, Geovanna Moreira (2020)
Housing of social interest (HIS) in Brazil is within a scenario of scarcity of resources, poorly meeting the broad and varied basic needs of users, causing a negative notion of well-being. In addition to showing low resilience, where the built environment absorbs and responds minimally to the impacts suffered, not promoting a positive adaptation of spaces. This work falls within the scope of institutional research: “[BER_HOME] Assessing The Built Environment Resilience in Brazilian Social Housing” and seeks to investigate the relevance and relationship of resilience in the built environment in HIS and the welfare of users, from the Ways to Wellbeing, through the Post-Occupation Assessment method for data collection in two housing estates in the city of Uberlândia, Minas Gerais. With the ultimate goal of providing users with solutions and strategies that contribute to well-being, increasing resilience in the built environment in which they live. To this end, tools will be developed to evaluate and disseminate results in a computational tools.